Factors of Public Interest in Investing in Gold Jewelry from an Islamic Economic Perspective in the Sekarbela Area - Dini Handayani; Busaini Busaini (Indonesian Development Economics and Localities, 2025)
Gold investment, especially in the form of jewelry, has a strategic role in the community's economy, especially in areas that have a strong tradition in gold trading such as Sekarbela, Mataram. However, the limited research that examines the factors of gold investment interest from an Islamic economic perspective makes this study important to understand community motivations as well as provide sharia-based recommendations. This study aims to determine the factors that influence community interest in investing in gold jewelry based on Islamic economic principles in the Sekarbela Area. The method used is qualitative with a participatory observation approach and in-depth interviews. The research location is in the Sekarbela Area, Mataram City, with informants selected using a purposive sampling technique. Data validity is strengthened through triangulation. The results of the study show that the majority of gold traders start their businesses with their own capital or loans, with a strong tendency to save and invest profits for business development. Psychological, social, and income level factors are the main drivers of investment interest. Although investment awareness has grown, the approach used is still traditional and based on personal trust. These findings contribute to the development of sharia financial literacy and strategies for strengthening halal investment in the community.